A systematic literature review on integrating contactless biometrics into online learning environments - Xaba, Samukeliswe Londeka; Aworinde, Halleluyah Oluwatobi; Niekerk, Brett van (Edelweiss Applied Science and Technology, 2025)
The rapid expansion of online learning platforms has created significant challenges in ensuring secure and seamless user authentication. Traditional methods, such as passwords and PINs, are vulnerable to security breaches and inefficiencies, prompting the exploration of contactless biometric technologies as viable alternatives. This systematic literature review examines the integration of contactless biometrics—such as facial recognition, voice patterns, and behavioral traits—into online learning environments, emphasizing their effectiveness, advantages, and challenges. This review analyzed 44 peer-reviewed studies from 2010 to 2024. Findings from the review show that contactless biometrics enhance security and user experience but face adoption barriers, such as privacy concerns, algorithmic biases, and technical limitations. Multimodal systems (e.g., combining facial recognition and keystroke dynamics) demonstrate promise in balancing accuracy and scalability, especially in high-stakes assessments. Ethical and regulatory frameworks, including GDPR compliance and bias mitigation, are crucial for responsible deployment. The study identifies gaps in research on Massive Open Online Courses (MOOCs) and underscores the urgent need for scalable, inclusive solutions. Recommendations include hybrid authentication models, inclusive design for diverse learners, and iterative testing to enhance fairness and usability. By synthesizing current advancements and challenges, this review provides actionable insights into the responsible integration of contactless biometrics in online learning for educators, developers, and policymakers. It contributes to the discourse on ethical deployment, regulatory compliance, and inclusive technological design, offering a foundation for future research and innovation in digital authentication.